Exploring the factors of enabling environments for business investment projects in rural communities: stakeholders’ perspectives - Shongwe, Mcolisi Austine; Lukhele, Themba Mfanafuthi; Zulu, Hlengiwe Patronella (Frontiers in Sustainable Cities, 2024)
In recent years, the Local Economic Development (LED) planning paradigm has gained widespread acceptance worldwide as a locality-based response to the challenges posed by globalization, devolution, and local-level opportunities and challenges. Noticeably, governments in the Global South are seen to be supporting linkage policies that directly couple profitable growth and investment with redistribution and community development in ruralbased localities. To attract potential investors to circulate more resources within the local rural communities, local governments must ensure that the Local Investment Climate (LIC) is functional for business investment. Unlike in the urban areas, rural localities by their nature of periphery location from economic development nodes, prospective Businesses Investment Projects (BIP) are often faced with delays and uncertainty. This is mainly because the factors underlying the enabling environments for business investment in rural localities are poorly understood and based on speculation. Against this backdrop, this study therefore set out to explore and unveil the key factors that are fundamental for ensuring a conducive and functionalLocal Investment Climate (LIC) in rural communities. Through a qualitative case study approach with the application of a conventional content analysis method, performed with coding methods, the study unveiled five key factors which were presented in a thematic approach. Namely, market and customer needs; government and regulatory support; access to infrastructure and services; land availability and zoning; and participatory community engagement. Understanding these fundamental factors which underpin conducive and operational investment environments is important for viable business decision-making in the feasibility study of investment projects towards LED in rural communities.